MUI DALAM MEMBENDUNG AJARAN MENYIMPANG (Metode Penyelesaikan Konflik Keagamaan di Kabupaten Gowa) - Yahya, Muhammad; Khalik, Subehan; Sakka, Abdul Rahman (Program Pascasarjana, UIN Alauddin Makassar, 2025)
The Indonesian Ulema Council (MUI) has strategic duties and functions as a servant of the people (khādim al-ummah), protector of society (ḥimāyat al-ummah), and partner of the government (ṣadīq al-ḥukūmah) in maintaining order and purity in religious life. These three roles are realized through various concrete steps to respond to the problems of the ummah that arise in society. In Gowa Regency, the emergence of religious issues that are localistic in nature and later identified as deviant teachings is a manifestation of individual religious interpretations that have developed evolutionarily. These deviations are apparent in aspects of belief in God, prophethood, attitudes, and ways of living in groups, giving rise to what can be called “free interpretations” of the authenticity of the Qur'an and Sunnah of the Prophet. Some of the teachings that have developed in this region include the teachings of the Grand Master who calls himself Tarekat Tajul Khalwatiyah Syekh Yusuf, as well as other teachings that are suspected of being deviant, namely the Teachings of Purity, which were identified in February 2023. This study aims to examine the factors causing the emergence of deviant teachings and the strategies of the Gowa Regency MUI in dealing with them. The results of the study show that the main triggers are internal factors, such as superficial faith and weak religious understanding among the community, as well as external factors, such as the doctrine of Sufi masters who build a relationship of worldly and spiritual dependence between master and disciple. The efforts made by the MUI include deepening information, tabayyun, studying indicators of heresy, involving Islamic organizations, coordinating with the government and law enforcement agencies, issuing fatwas, disseminating information, and taking preventive measures through institutional guidance at the sub-district level. These efforts demonstrate the central role of the MUI in maintaining the stability of religious life in Gowa Regency.